Choice Preference of Middle-Aged and Elderly People on Integrated Medical Services and Elderly Care Model: A Cross-Sectional Study - Shangren Qin PhD; Mengqiu Zhou MM; Yenuan Cheng MM; Junjie Zhao MM; Ye Ding MM (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2024)
Facing the increasingly severe aging situation, China has started to implement the “integrated medical services and elderly care (IMSEC)” policy, which covers a variety of IMSEC models. However, there is currently little research on middle-aged and elderly people’s choice preference for these IMSEC models and their associated factors. Through the face-to-face questionnaire method, the choice preference of middle-aged and elderly people aged 45 years and over in Zhejiang Province, China, to the IMSEC model is explored. Through the multinomial logistic regression model, the influencing factors of choice preference are analyzed. A total of 1034 people are included in 2022. Their choice preference for the 4 major types of IMSEC models are Home IMSEC model (48.07%), Community IMSEC model (23.79%), Institutional IMSEC model (21.76%), and Internet Plus IMSEC model (6.38%). “C1. Home elderly care and contracted with a family doctor” is the most chosen subtype, accounting for 34.53%. The rural elderly are more likely to choose “Home IMSEC model” (OR(95%CI) = 2.977(1.343-6.601)). Elderly people with relatively large life care needs are more likely to choose “Institutional IMSEC model” (OR(95%CI) = 1.114(1.042-1.190)). Moreover, age, education, and self-reported health status are also influencing factors of choice preference. The government should focus on promoting the development of the “Home IMSEC model” and increase the promotion of “Internet Plus IMSEC model.” In addition, the life care service capacity and spiritual comfort capacity of IMSEC institutions, as well as the medical service capacity of the community, need to be enhanced.